Tensile-dominant fractures observed in hydraulic fracturing laboratory experiment using eagle ford shale. Issue 2 (20th April 2020) - Naoi, Makoto; Chen, Youqing; Yamamoto, Kazune; Morishige, Yuya; Imakita, Keiichi; Tsutumi, Naofumi; Kawakata, Hironori; Ishida, Tsuyoshi; Tanaka, Hiroyuki; Arima, Yutaro; Kitamura, Shigehiro; Hyodo, Daisuke
SUMMARY: Hydraulic fracturing plays a vital role in the development of unconventional energy resources, such as shale gas/oil and enhanced geothermal systems to increase the permeability of tight rocks. In this study, we conducted hydraulic fracturing experiments in a laboratory using carbonate-rich outcrop samples of Eagle Ford shale from the United States. We used a thermosetting acrylic resin containing a fluorescent compound as a fracturing fluid. Immediately after fracturing, the liquid resin penetrated in the fractured blocks was hardened by applying heat. Then, the crack was viewed under UV irradiation, where the fluorescent resin allowed the induced fracture to be clearly observed, indicating the formation of simple, thin bi-wing planar fractures. We observed the detailed structure of the fractures from microscopy of thin cross-sections, and found that their complexity and width varied with the distance from the wellbore. This likely reflects the change in the stress state around the tip of the growing fracture. The interaction between fractures and constituent grains/other inclusions (e.g. organic substances) seemed to increase the complexity of the fractures, which may contribute to the efficient production of shale gas/oil via hydraulic fracturing. We first detected acoustic emission (AE) signals several seconds before the peak fluid pressure was observed, and the active region gradually migrated along the microscopically observed fracture with increasing magnitude. Immediately after the peak pressure was observed, the fluid pressure dropped suddenly (breakdown) with large seismic waves that were probably radiated by dynamic propagation of the fracture; thereafter, the AE activity stopped. We applied moment tensor inversion for the obtained AE events by carefully correcting the AE sensor characteristics. Almost all of the solutions corresponded to tensile events that had a crack plane along the maximum compression axis, as would be expected based on the conventional theory of hydraulic fracturing. Such domination of tensile events has not been reported in previous studies based on laboratory/ in situ experiments, where shear events were often dominant. The extreme domination of the tensile events in the present study is possibly a result of the use of rock samples without any significant pre-existing cracks. Our experiments revealed the fracturing behaviour and accompanying seismic activities of very tight rocks in detail, which will be helpful to our understanding of fracturing behaviour in shale gas/oil resource production.